Elucidating the efficacy of vaccination against Vibriosis in Lates calcarifer using two recombinant protein vaccines containing the Outer Membrane Protein K (r-OmpK) of Vibrio alginolyticus and the DNA Chaperone J (r-DnaJ) of Vibrio harveyi - Silvaraj, Santha; Md Yasin, Ina Salwany; Abd Karim, Murni Marlina; Saad, Mohd Zamri (Multidisciplinary Digital Publishing Institute, 2020)
Recombinant cell vaccines expressing the OmpK and DnaJ of Vibrio were developed and subsequently, a vaccination efficacy trial was carried out on juvenile seabass (~5 cm; ~20 g). The fish were divided into 5 groups of 50 fish per group, kept in triplicate. Groups 1 and 2 were injected with 107 CFU/mL of the inactivated recombinant cells vaccines, the pET-32/LIC-OmpK and pET-32/LIC-DnaJ, respectively. Group 3 was similarly injected with 107 CFU/mL of inactivated E. coli BL21 (DE3), Group 4 with 107 CFU/mL of formalin killed whole cells V. harveyi, and Group 5 with PBS solution. Serum, mucus, and gut lavage were used to determine the antibody levels before all fish were challenged with V. harveyi, V. alginolyticus, and V. parahemolyticus, respectively on day 15 post-vaccination. There was significant increase in the serum and gut lavage antibody titers in the juvenile seabass vaccinated with r-OmpK vaccine. In addition, there was an up-regulation for TLR2, MyD88, and MHCI genes in the kidney and intestinal tissues of r-OmpK vaccinated fish. At the same time, r-OmpK triggered higher expression level of interleukin IL-10, IL-8, IL-1ß in the spleen, intestine, and kidney compared to r-DnaJ. Overall, r-OmpK and r-DnaJ triggered protection by curbing inflammation and strengthening the adaptive immune response. Vaccinated fish also demonstrated strong cross protection against heterologous of Vibrio isolates, the V. harveyi, V. alginolyticus, and V. parahaemolyticus. The fish vaccinated with r-OmpK protein were completely protected with a relative per cent of survival (RPS) of 90 percent against V. harveyi and 100 percent against V. alginolyticus and V. parahaemolyticus. A semi-quantitative PCR detection of Vibrio spp. from the seawater containing the seabass also revealed that vaccination resulted in reduction of pathogen shedding. In conclusion, our results suggest r-OmpK as a candidate vaccine molecule against multiple Vibrio strain to prevent vibriosis in marine fish.